OCCURRENCE OF OILSARDINE IN THE SPAWNING STAGE OFF VIZHINJAM - Lazarus, S (Indian Journal of Fisheries, 2011)
The occurrence of ripe and spawning oilsardine, Sardinella longiceps Val.off Vizhinjam is reported for the first time. Ova-diameter studies reveal a bdmodaldistribution of ova and fecundity estimates of the primary and secondarymodes were about 46.000 and 88,000 ova respectively